Analysis of National Security Strategies in Response to Conflicts and Competition over Oil Resources in the Indo-Pacific Region - Rizal, Tulus Afriyan; Madjid, Adnan; Uksan, Arifuddin (International Journal of Education, Vocational and Social Science, 2025)
The Indo-Pacific region has become the focal point of global geopolitical competition, involving major powers such as the United States, China, India, and Japan. The background of this study stems from the escalating rivalry and contest over oil resources in the region, which directly affects national security and regional stability, including that of Indonesia. The main objective of this research is to analyze the geopolitical dynamics, energy competition, and their implications for Indonesia’s national defense doctrine within the framework of the Indo-Pacific Strategy and the ASEAN Outlook on the Indo-Pacific (AOIP). This study employs a qualitative descriptive approach through an extensive literature review of international and national academic sources focusing on geopolitics and energy security. The findings indicate that the struggle for energy resources in the Indo-Pacific not only influences economic relations but also shapes the direction of national defense and diplomatic strategies. Consequently, Indonesia must renew its defense doctrine with a focus on maritime defense, energy security, and regional multilateral cooperation to safeguard sovereignty and maintain stability in the Indo-Pacific region.